PREFERENSI SISWA EFL TERHADAP GURU BAHASA INGGRIS YANG BAIK - Setiadi, Muhammad Ikhsan; Febriyanti, Emma Rosana (Universitas Putera Batam, 2023)
The process of teaching is a continuous learning journey, even with years of experience in teaching English as a foreign language, it is difficult to determine how to be an effective teacher. Different learners and teachers have also different views on what constitutes a